(untitled) (Journal of Comilla Medical College Teachers’ Association, 2025)
Background: Acinetobacter baumannii causes serious nosocomial infections, and is associated with high morbidity and mortality. Objective: The objective of this study was to determine the prevalence of Acinetobacter baumanii infection in patients at Dhaka Medical College Hospital and to estimate antimicrobial resistance pattern among the Acinetobacter baumannii isolates. Method: During the study period from January 2022 to December 2022, 400 clinical samples, including endotracheal aspirates, wound swab and pus, blood, sputum, urine were collected and analyzed from patients admitted and visiting outpatient department of various ward in Dhaka Medical College Hospital, Dhaka. Result: Out of 400 clinical samples, 275(68.8%) yielded growth. Among them 50 were Acinetobacter spp. Thirty-nine samples were confirmed as Acinetobacter baumannii through PCR by detection of blaOXA -51 like gene, and the prevalence of Acinetobacter baumannii was 14.2%. The highest (89.7%) number of Acinetobacter baumannii samples showed resistance to amoxiclav, ceftazidime and ciprofloxacin and least to colistin (30.8%). Conclusion: The results of this study could help our clinicians create a local antibiogram in the fight against Acinetobacter baumannii infections. J Com Med Col Teachers’ Asso Jan 2025; 29(1):15-19